Genotoxic and Cytotoxic Effects in Exfoliated Buccal and Nasal Cells of Chromium and Cobalt Exposed Electroplaters - Wultsch, Georg; Nersesyan, Armen; Kundi, Michael; Mišík, Miroslav; Setayesh, Tahereh; Waldherr, Monika; Vodicka, Pavel; Vodickova, Ludmila; Knasmüller, Siegfried (Journal of toxicology and environmental health. Part A, 2017)
Results of a number of studies indicate that electroplaters have increased cancer risks as a consequence of exposure to genotoxic metals such as chromium (VI) and nickel. These effects may be due to induction of damage of the genetic material which plays a key role in the etiology of cancer, and it was found that workers in galvanization factories exhibited increased levels of DNA damage. The aim of the present study was to investigate genetic stability in workers of a bright plating factory who are exposed to chromium (Cr) and cobalt (Co). Exfoliated cells were collected from the buccal and nasal mucosa of workers (n = 42) and matched controls (n = 43) and analyzed for induction of micronuclei (MN) which are formed as a consequence of chromosomal aberrations. In addition, other nuclear anomalies namely nuclear buds (Nbuds) which are formed as a consequence of gene amplification and markers indicating different stages of cell death (condensed chromatin, karyorrhexis, karyolysis, and pyknosis) were also assessed. No evidence was noted for induction of MN, but significantly increased rates of Nbuds in cells from both, buccal and nasal mucosa, were found. Parameters which are indicative for cytotoxic effects were more pronounced in nasal cells and rose with duration of employment period. Overall, our findings indicated that no apparent chromosomal damage occurred in bright electroplaters. However, data demonstrated that acute cytotoxic effects may lead to inflammations and/or lesions in epithelia of the respiratory tract of the workers.
Keywords: Micronuclei, Chromosome-Defective; lidské chromozomy; Adult; pokovování galvanické; Male; lidé; mikrojádra chromozomálně defektní; Humans; Cell Death; buněčná smrt; pracovní expozice; chrom; Occupational Exposure; Cell Nucleus; kobalt; ústní sliznice; mužské pohlaví; Cobalt; Mouth Mucosa; dospělí; Chromosomes, Human; buněčné jádro; Electroplating; ženské pohlaví; Female; nosní sliznice; Chromium; Nasal Mucosa